The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/nar/gkz256
|View full text |Cite
|
Sign up to set email alerts
|

A new function of copper zinc superoxide dismutase: as a regulatory DNA-binding protein in gene expression in response to intracellular hydrogen peroxide

Abstract: In microorganisms, a number of metalloproteins including PerR are found to regulate gene expression in response to environmental reactive oxygen species (ROS) changes. However, discovery of similar regulatory mechanisms remains elusive within mammalian cells. As an antioxidant metalloenzyme that maintains intracellular ROS homeostasis, copper zinc superoxide dismutase (SOD1) has high affinity for DNA in solution and in cells. Here, we explored the regulatory roles of SOD1 in the expression of genes in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Recently it has been demonstrated that SOD1 acts as a H 2 O 2 -responsive regulatory protein in the expression of ALS-linked genes. Both sequence preference and affinity of SOD1 interactions with DNA depend on SOD1 conformation 21 . Thereby, PTCs that escape NMD in SOD1 are expected to cause toxic conformational changes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been demonstrated that SOD1 acts as a H 2 O 2 -responsive regulatory protein in the expression of ALS-linked genes. Both sequence preference and affinity of SOD1 interactions with DNA depend on SOD1 conformation 21 . Thereby, PTCs that escape NMD in SOD1 are expected to cause toxic conformational changes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the oxidative lesions in DNA there are not only strand breaks but also base modifications, sugar damage, and abasic sites [29]. Due to the ability of oxidants, antioxidants and other determinants of the intracellular redox state to modulate gene transcription, ROS changes within mammalian cells can also modify the expression of numerous mammalian genes, such as oncogenes and amyotrophic lateral sclerosis-linked genes during transcription, as recently demonstrated by Li [30].…”
Section: Introductionmentioning
confidence: 93%
“…Tsang et al [14] found that in response to toxic levels of oxidative stress (0.4 mM H 2 O 2 ), SOD1 translocates to the nucleus to transcriptionally upregulate antioxidant genes. In addition, this new nuclear function of SOD1 was recently shown to involve direct SOD1-DNA interactions with specific DNA sequence preferences [15]. The nuclear translocation of SOD1 is dependent on activation of ATM/Mec1 by ROS, which promotes SOD1 binding to the Chk2-related kinase, Dun1.…”
Section: Phosphorylationmentioning
confidence: 99%
“…These findings suggest that the large majority of SOD1 (>99%) may be required for functions outside its canonical role in dismutating superoxide. Indeed, SOD1 is reported to function in cellular zinc [12] and copper buffering [13], as a nuclear transcription factor to control the expression of antioxidant genes [14,15] and for peroxide-mediated redox signaling [11].…”
Section: Introductionmentioning
confidence: 99%